The Impact of Organizational Injustice on the Work Turnover among Faculty Members in Jordanian Public Universities - Al Maaitah, Angham Saleem; Al- Bashabshah, Samer Abdul Majid (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to analyze the impact of organizational injustice on turnover among faculty members in Jordanian public universities. To achieve the objectives of the study, a questionnaire was developed for the purpose of data collection, the sample size was (739) respondents, (631) participants responded who represented (85.4%) of the original sample. Which was chosen in Were selected in a random stratified random sampling method. the study uses in the analysis of the study data descriptive statistics and analytical statistics method. The study found a set of results, the most important of which were: • The perceptions of faculty members in Jordanian public universities toward the organizational injustice and turnover dimensions came a high degree. • There is an impact of organizational injustice dimensions in turnover dimensions which explains (63.8%) of variation in the dependent variable (turnover dimensions). • There are statistically significant differences at level (α≤0.05) in organizational injustice and turnover due to demographic variables (Gender, type of college, age, education level, experience, academic level) The study reached a set of recommendations, the most important of which are: The need to improve the system of incentives, material, moral rewards and evaluation standards, activating participation in scientific conferences and symposia, participating in decision- making, and spreading the concepts of transparency and the right and linking it to duty in Jordanian universities. Spread the spirit of direct and positive relations in order to reduce the turnover rate.